Numerical investigation of the effect of process parameters during Aluminium wheel flow-forming - Hwang, So Young (Strojniški vestnik, 2015)
Aluminium wheel flow-forming is an incremental forming technique that lengthens the material in the axial direction and thins it in the radial direction. There are many advantages to wheel flow-forming, including reducing the weight of the product, which leads to improved fuel economy. However, in terms of geometric accuracy, it is difficult to manufacture with high precision. In this study, process conditions, such as headstock load, feed rate, and radial compression, as well as the geometry of the rolls, are investigated to improve the precision of the product. To do this, a simulation was performed with SHAPE-RR, a type of FEM software. The result of the FE analysis was verified by comparing the bulging amount of the wheel. The material property of aluminium was determined through a hot compression test. As a result, geometric accuracy was improved by increasing the feed rate of the rolls. Moreover, applying a lower compression amount in the radial direction for the third roll increased the geometric precision.
Keywords: finite element method; geometrijska točnost; metoda končnih elementov; napaka povratnega toka; potisno oblikovanje aluminija; stopnja stiskanja; Taguchijeva metoda